Measuring ERP System Readiness with COBIT 2019 at IT Vendor Industry - Muhamad Calvin Syah Putra; Jansen Wiratama; Agus Sulaiman (Universitas Islam Raden Rahmat, Malang, 2024)
The application of information technology that supports company business activities in IT services can be assessed for its IT governance capabilities using the COBIT 2019 framework, including security aspects. This research aims to determine the company's IT governance capabilities in the Managed Risk (APO12), Managed Security (APO13), and Managed Configuration (BAI10) domains to overcome security risks and provide recommendations for achieving a higher level of capability. This qualitative research uses data obtained through interviews and literature studies. Based on the results of capability measurements, the company received a score at level 2 to target levels 3 and 4, which indicates a gap of 1 to 2 levels. Recommendations include improving risk understanding, security awareness, security controls, and configuration management. Additionally, recommendations for ERP modules such as risk management, information security management, project management, configuration management, and quality management are proposed to address the identified issues.